Association between residential greenspace structures and frailty in a cohort of older Chinese adults - Qile He; Hao-Ting Chang; Chih-da Wu; John S. Ji (Communications Medicine, 2022)
Plain language summary Areas dominated by vegetation (greenspaces) are associated with reduced frailty, an aging-related decline in physical function. Here, we aimed to look at the association between specific greenspace structures and frailty in a cohort of older Chinese adults. We use demographic and health data from a 6-year survey and greenspace structure data from satellites to conduct our statistical analysis. We find that a larger area, more complex shape, more concentrated greenspaces, and greater proximity might lower levels of frailty, especially in females, people aged 100 and above, illiterate people, city residents, unmarried people, and individuals with increased frailty. These findings help us to understand how the environment impacts our health and how we might mitigate frailty in older aged adults.